Circulating Concentrations of Cathelicidin Anti-Microbial Peptide (CAMP) Are Increased during Oral Glucose Tolerance Test - Höpfinger, Alexandra; Karrasch, Thomas; Schäffler, Andreas; Schmid, Andreas; Justus Liebig University Giessen (My University, 2023)
Recent investigation has revealed the significant role of Cathelicidin antimicrobial peptide (CAMP) in infection defense and innate immunity processes in adipose tissue. Meanwhile, knowledge of its regulation and functions in metabolic contexts as an adipokine remains sparce. The present study investigated the postprandial regulation of circulating CAMP levels during oral glucose tolerance tests (OGTTs). Eighty-six metabolically healthy volunteers participated in a standardized 75 g-2 h-OGTT setting. The effects of exogenous glucose, insulin, and incretins on CAMP expression in human adipocyte culture (cell-line SGBS) were studied in vitro. CAMP concentrations in blood serum samples were measured by ELISA techniques and adipocyte gene expression levels were quantified by real-time PCR. Of note, base-line CAMP serum quantities were negatively correlated with HDL cholesterol levels as well as with the anti-inflammatory adipokine adiponectin. During the 2 h following glucose ingestion, a significant rise in circulating CAMP concentrations was observed in considerable contrast to reduced quantities of fatty acid binding proteins (FABP) 2 and 4 and dipeptidyl peptidase 4 (DPP4). In SGBS adipocytes, neither differing glucose levels nor insulin or incretin treatment significantly induced CAMP mRNA levels. According to our data, glucose represents a positive postprandial regulator of systemic CAMP. This effect apparently is not mediated by the regulatory impact of glucose metabolism on adipocyte CAMP expression.
Keywords: ddc:630